Extraction of anthocyanins from grape by-products assisted by ultrasonics, high hydrostatic pressure or pulsed electric fields: a comparison - Corrales Moreno, Margarita; Toepfl, Stefan; Butz, Peter; Knorr, Dietrich; Tauscher, Bernhard (Innovative food science & emerging technologies, 2008)
Extracts from grape by-products contain bioactive substances such as anthocyanins which could be used as natural antioxidants or colourants. The effect of heat treatment at 70 °C combined with the effect of different emerging novel technologies such as ultrasonics (35 KHz), high hydrostatic pressure (600 MPa) (HHP) and pulsed electric fields (3 kV cm−1) (PEF) showed a great feasibility and selectivity for extraction purposes. After 1 h extraction, the total phenolic content of samples subjected to novel technologies was 50% higher than in the control samples. Therefore, the application of novel technologies increased the antioxidant activity of the extracts being the extractions carried out with PEF four-fold, with HHP three-fold and with ultrasonics two-fold higher than the control extraction. In addition, the extraction of individual anthocyanins was studied showing a selective extraction based on the glucose moieties linked to the anthocyanidins; anthocyanin monoglucosides were better extracted by PEF, whereas the acylated ones were extracted by HHP. - Industrial relevance - This study examines the feasibility of different emerging technologies such as high hydrostatic pressure, pulsed electric fields and ultrasonics as potential extraction methods for bioactive substances from grape by-products. Grape by-products represent a low-cost source of valuable bioactive compounds such as anthocyanins, with great industrial applications as colourants or nutraceuticals. The higher yields obtained in extractions carried out by high hydrostatic pressure and pulsed electric fields are of major interest from an industrial point of view, since solvent amounts were reduced and extraction times shortened. Thus, the combination of emerging technologies for extraction purposes and low-cost raw materials is an economical alternative to traditional extraction methods according to industry demands and a sustainable development.